1992
DOI: 10.1007/bf01961247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of binding of cytotoxic analogs of luteinizing hormone-releasing hormone to human breast cancer and mouse MXT mammary tumor

Abstract: The binding characteristics of several cytotoxic analogs of luteinizing hormone-releasing hormone (LH-RH) developed in our laboratory were examined in membranes from human breast cancer and estrogen independent MXT mammary cancer. Specific binding of [125I]D-Trp6-LH-RH and the cytotoxic LH-RH analog [125I]T-98 ([D-Lys6]LH-RH coupled to glutaryl-2-(hydroxymethyl)anthraquinone) (HMAQG) was demonstrated in membrane preparations from human breast and MXT mammary tumor cells. Ligand binding of T-98 was specific, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…20 Recently, we showed that our modern cytotoxic LH-RH analogs, AN-152 and AN-207, which contain the same carrier, have high binding affinity to LH-RH receptors in membrane preparations from human breast carcinomas and MCF-7 and MDA-MB-231 cell lines. 16 We have also demonstrated that AN-207 hybrid fully preserves the high binding affinity of the carrier peptide [D-Lys 6 ]LH-RH to rat pituitary membranes.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recently, we showed that our modern cytotoxic LH-RH analogs, AN-152 and AN-207, which contain the same carrier, have high binding affinity to LH-RH receptors in membrane preparations from human breast carcinomas and MCF-7 and MDA-MB-231 cell lines. 16 We have also demonstrated that AN-207 hybrid fully preserves the high binding affinity of the carrier peptide [D-Lys 6 ]LH-RH to rat pituitary membranes.…”
Section: Discussionmentioning
confidence: 99%
“…An inhibition in cellular tumor growth has been observed in breast cancer. 3 10 Physiologically, in pituitary gland, the gonadotropin receptor (GnRH) signaling is mediated through the G-protein α q . These proteins conduct the subsequent activation of phopholipase C (PLC) that catalyzes the hydrolysis of membrane phospholipids generating the liberation of intracellular Ca 2+ .…”
Section: Lhrh Agonists: Biology and Antitumoral Effectmentioning
confidence: 99%
“…The conjugates exhibited a wide range of specific binding affinities toward GnRH receptors. The cytotoxicity of some peptidedrug hybrids was markedly augmented, in vitro, far beyond that of the drug component itself (25)(26)(27).…”
Section: Figurementioning
confidence: 99%